Biocatalytic reduction of α, β-unsaturated carboxylic acids to allylic alcohols. Issue 12 (1st June 2020) - Aleku, Godwin A.; Roberts, George W.; Leys, David
Abstract : Robust in vitro and in vivo carboxylic acid reductase (CAR)-based biocatalytic systems have been developed that enable hydrogenation of α, β-unsaturated carboxylic acids to allylic alcohols and their saturated analogues. Abstract : We have developed robust in vivo and in vitro biocatalytic systems that enable reduction of α, β-unsaturated carboxylic acids to allylic alcohols and their saturated analogues. These compounds are prevalent scaffolds in many industrial chemicals and pharmaceuticals. A substrate profiling study of a carboxylic acid reductase (CAR) investigating unexplored substrate space, such as benzo-fused (hetero)aromatic carboxylic acids and α, β-unsaturated carboxylic acids, revealed broad substrate tolerance and provided information on the reactivity patterns of these substrates. E. coli cells expressing a heterologous CAR were employed as a multi-step hydrogenation catalyst to convert a variety of α, β-unsaturated carboxylic acids to the corresponding saturated primary alcohols, affording up to >99% conversion. This was supported by the broad substrate scope of E. coli endogenous alcohol dehydrogenase (ADH), as well as the unexpected CC bond reducing activity of E. coli cells. In addition, a broad range of benzofused (hetero)aromatic carboxylic acids were converted to the corresponding primary alcohols by the recombinant E. coli cells. An alternative one-pot in vitro two-enzyme system, consisting of CAR and glucose dehydrogenase (GDH), demonstrates promiscuous carbonyl reductase activity of GDH towards a wide range of unsaturated aldehydes. Hence, coupling CAR with a GDH-driven NADP(H) recycling system provides access to a variety of (hetero)aromatic primary alcohols and allylic alcohols from the parent carboxylates, in up to >99% conversion. To demonstrate the applicability of these systems in preparative synthesis, we performed 100 mg scale biotransformations for the preparation of indole-3-aldehyde and 3-(naphthalen-1-yl)propan-1-ol using the whole-cell system, and cinnamyl alcohol using the in vitro system, affording up to 85% isolated yield.